Direct access cancer testing in primary care: a systematic review of use and clinical outcomes - Friedemann Smith, C; Tompson, A; Jones, N; Brewin, J; Spencer, E; Bankhead, C; Hobbs, F; Nicholson, B (Royal College of General Practitioners, 2018)
Background Direct access (DA) testing allows GPs to refer patients for investigation without consulting a specialist. The aim is to reduce waiting time for investigations and unnecessary appointments, enabling treatment to begin without delay. Aim To establish the proportion of patients diagnosed with cancer and other diseases through DA testing, time to diagnosis, and suitability of DA investigations. Design and setting Systematic review assessing the effectiveness of GP DA testing in adults. Method MEDLINE, Embase, and the Cochrane Library were searched. Where possible, study data were pooled and analysed quantitatively. Where this was not possible, the data are presented narratively. Results The authors identified 60 papers that met pre-specified inclusion criteria. Most studies were carried out in the UK and were judged to be of poor quality. The authors found no significant difference in the pooled cancer conversion rate between GP DA referrals and patients who first consulted a specialist for any test, except gastroscopy. There were also no significant differences in the proportions of patients receiving any non-cancer diagnosis. Referrals for testing were deemed appropriate in 66.4% of those coming from GPs, and in 80.9% of those from consultants; this difference was not significant. The time from referral to testing was significantly shorter for patients referred for DA tests. Patient and GP satisfaction with DA testing was consistently high. Conclusion GP DA testing performs as well as, and on some measures better than, consultant triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction.